2015
DOI: 10.1007/s12640-015-9572-6
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Involvement of Retinoid X Receptors in DDE Neurotoxicity

Abstract: Dichlorodiphenyldichloroethylene (DDE) is a primary environmental and metabolic degradation product of the pesticide dichlorodiphenyltrichloroethane (DDT). It is one of the most toxic compounds belonging to organochlorines. DDE has never been commercially produced; however, the parent pesticide DDT is still used in some developing countries for disease-vector control of malaria. DDT and DDE remain in the environment because these chemicals are resistant to degradation and bioaccumulate in the food chain. Littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…p,p'-DDE is a breakdown product of the insecticide dichlorodiphenyltrichloroethane (DDT), well-known for its anti-androgenic activities [59]. Populationbased studies have shown that men with adult [60] or prenatal [61] DDE exposure were sub-fertile [62] and were also associated with impairment of cognitive functions, deficits in psychosocial developments in childhood [63][64][65][66][67], and increased risk of neural degenerative diseases at old age [68]. nPFOS belongs to a group of substances that are widely used in a variety of products including surface treatments for stain resistance, surface treatments on metals, as well as firefighting foams.…”
Section: Discussionmentioning
confidence: 99%
“…p,p'-DDE is a breakdown product of the insecticide dichlorodiphenyltrichloroethane (DDT), well-known for its anti-androgenic activities [59]. Populationbased studies have shown that men with adult [60] or prenatal [61] DDE exposure were sub-fertile [62] and were also associated with impairment of cognitive functions, deficits in psychosocial developments in childhood [63][64][65][66][67], and increased risk of neural degenerative diseases at old age [68]. nPFOS belongs to a group of substances that are widely used in a variety of products including surface treatments for stain resistance, surface treatments on metals, as well as firefighting foams.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic cells were stained with Hoechst 33342 after 24 h, as previously described [ 38 ]. The neocortical cells cultured on glass cover slips were washed with 10 mM phosphate-buffered saline (PBS) and exposed to the stain (0.6 mg/ml), at room temperature for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the methylation statuses of the DNA in the neocortical cells that were exposed to triclocarban, an Imprint Methylated DNA Quantification Kit was utilized. The capture and detection antibodies detected the methylated DNA that was quantified colorimetrically as previously described [ 38 40 ]. The purified DNAs were added to a 96-well plate (150 ng/well) where they bound with the capture antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Compound 12 is also used as a tool to investigate the influence of environmental hormones on RXR. For example, the mechanism of neurotoxicity by dichlorodiphenyldichloroethylene (DDE), 61 the effect of tributyltin on osteogenesis, 62 and the toxicity of organotin 63 were found to involve transcriptional activation of RXR.…”
Section: Latest Research On Rxr Antagonistsmentioning
confidence: 99%